The experiences of attending an international veteran sporting competition and preparatory camp for Team Ukraine during the Russo-Ukrainian conflict - Castle, Claire L.; Heinze, Nikki; Gomes, Renata S. M. (Frontiers in Sports and Active Living, 2024)
IntroductionThis article offers unique insight into Team Ukraine's experiences of attending an international sporting event for veterans living with disability and injured active-duty personnel (the United States' Department of Defense Warrior Games, “The Games”) and a 5-week preparatory camp in the United Kingdom (UK).MethodsA survey gathered qualitative data at three time points: during the second and final week of training camp, and the in the two weeks immediately following participation at The Games. Forty-four out of 55 members of Team Ukraine (including veterans, active-duty personnel, support staff, and family members) provided responses in Survey 1, 20 in Survey 2, and 18 in Survey 3. These responses were thematically analysed to explore experiences and motivations for participation.Results and discussionFive main themes were identified: Rest and recuperation; The ongoing conflict as a source of motivation; The sporting experience; Veterans in sport; and Relationships. Whilst physically demanding, the camp was an opportunity for respite and emotional processing, and participants reflected on social benefits and improvements to physical health and sporting abilities. Perhaps of greatest significance was the role of the ongoing conflict in their motivations to attend The Games. The conflict brought participants together in their collective goals of representing Ukraine on an international stage, raising awareness of the war, and demonstrating strength through sporting success. Findings highlight the challenges experienced and overcome by Team Ukraine and provides insight into the role that competitive sporting events may play during times of conflict as a means of demonstrating national strength and pride, and meeting individuals' health and well-being needs.